2012
DOI: 10.2485/jhtb.21.367
|View full text |Cite
|
Sign up to set email alerts
|

So-Called ^|^ldquo;Denture Fibroma^|^rdquo;: A Retrospective Clinico-Pathological Study and Review of Literatures

Abstract: Abstract:The purpose of this study was to determine the clinico-pathological characteristics of so-called "denture fibroma" and to perform a review of literature. A comparative analysis was carried out to clarify the epidemiological characteristics of the lesion. A total of 142 cases (average age of 65.2 ± 11.1 years), predominantly female, with so-called "denture fibroma" was examined. The residual alveolar ridge in the posterior region (43.7 %) and in the anterior region (43.0 %) was affected with almost the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In the first step of the PCR assay, we used the degenerate L1 consensus primers GP5/6 18) and GP5+/6+ 19) , which can detect the presence of DNA of 9 HR-HPV types (16,18,31,33,35,45, 51, 56 and 58) and seven LR-HPV types (1,6,8,11,13,30,32 and 58) ( Table 1). Secondly, the positive PCR samples in the first step of the assay were analyzed by type-specific PCR with primers designed for the detection of HPV types 6, 11, 16, 18 and 33 13) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step of the PCR assay, we used the degenerate L1 consensus primers GP5/6 18) and GP5+/6+ 19) , which can detect the presence of DNA of 9 HR-HPV types (16,18,31,33,35,45, 51, 56 and 58) and seven LR-HPV types (1,6,8,11,13,30,32 and 58) ( Table 1). Secondly, the positive PCR samples in the first step of the assay were analyzed by type-specific PCR with primers designed for the detection of HPV types 6, 11, 16, 18 and 33 13) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Some investigators have reported that HPV infection is related to certain factors, including the sexual act, gender, age, smoking habit, alcohol consumption and denture wearing [9][10][11][12][13] . Denture epulis has been described as denture fibroma, epulis fissuratum, denture fibrosis, denture injury tumor, or hyperplasia from denture irritation 7,[14][15][16] . Clinically, and histopathologically, this lesion is a product of constant trauma and inflammation resulting from pressure on the denture flange [14][15][16] .Although HPV infection has been detected in the hyperplastic epithelium of denture fibroma 17) …”
Section: Introductionmentioning
confidence: 99%